POSITION OF GRANT DEEDS IN THE CASE OF SUPREME COURT DECISION NUMBER 175/K/PDT/2021 - M. Remon Septariawan; Yuliandri Yuliandri; Delfiyanti Delfiyanti (Warmadewa Press, 2025)
A grant of land rights is a gift from one person to another person without any compensation and is done voluntarily, without any contravention from the recipient of the gift and the gift takes place while the grantor is still alive. The act of granting land rights must be done before the PPAT with a Grant Deed is made which is the basis for registering land rights at the Regency/City Land Office. The problems that will be discussed in this research are first, what is the position of the grant deed in relation to the Supreme Court Decision Number 175/K/PDT/2021 in Papua, Second, what are the challenges in the Supreme Court Decision Number 175/K/PDT/2021. The aim of the research is to examine and analyze the position of grant deeds in the case of Supreme Court Decision Number 175/K/PDT/2021 in Papua and to study and analyze the challenges in Supreme Court Decision Number 175/K/PDT/2021 in Papua. This legal research is normative juridical research, namely normative juridical research referring to legal norms contained in laws and regulations and court decisions as well as legal norms that exist in society. The results of the research, the Land Deed Making Officer must put the grant agreement in the form of a PPAT deed, namely a grant deed as explained that every grant of land must be made with a PPAT deed as mentioned in Article 37 and Article 39 Paragraph 1 of Government Regulation Number 24 of 1997, making In the grant deed, it was seen that in the process of making the grant deed there were things that did not comply with the applicable regulations. Ms. Analyst Demotekay, who is the grant giver, said that she had never given the grant to Susilawati and there was no agreement between Ms. Analyst Demotekay and Martius Semuel Darinya, so this means that it can be suspected that there was engineering in this legal action on the part of the recipient of the grant. A series of legal cases involving fake grants, Mrs. Analis Demotekay and Martius Semuel, found that there was negligence and inaccuracy of PPAT Puspo Adi Cahayo S.H., M.Kn in making the Deed of Grant which resulted in the transfer of land rights to Susilawati's property.